2015
DOI: 10.1021/la503913z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization of Colloidal PbS Quantum Dots into Highly Ordered Superlattices

Abstract: X-ray structural analysis, together with steady-state and transient optical spectroscopy, is used for studying the morphology and optical properties of quantum dot superlattices (QDSLs) formed on glass substrates by the self-organization of PbS quantum dots with a variety of surface ligands. The diameter of the PbS QDs varies from 2.8 to 8.9 nm. The QDSL's period is proportional to the dot diameter, increasing slightly with dot size due to the increase in ligand layer thickness. Removal of the ligands has a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…We can speculate that the removal of oleic acid during the ligand exchange plays a crucial role for the film formation. It has been recently shown that the amount of oleic acid can influence the self-organization of QD superstructures [37][38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%
“…We can speculate that the removal of oleic acid during the ligand exchange plays a crucial role for the film formation. It has been recently shown that the amount of oleic acid can influence the self-organization of QD superstructures [37][38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Optical, electrical, thermal and mechanical properties of such QDSLs are thus determined not only by individual QDs, but also by the dimensionality dependent resonant couplings through the interior nano space among adjacent QDs tuned by ligand engineering down to subnanometer regime. 3,14,19,[31][32][33][34][35][36][37][38] Thus, the dimensionality in the QDSLs should be a crucial parameter for independent tailoring of the electronic and photoexcited properties including the multiple exciton generation (MEG) through which multiple electron-hole pairs can be produced; [39][40][41] the MEG is expected to increase solar cell efficiency by creating multiple carriers from a single photon absorption. 42 Meanwhile, temperature can be another important parameter to control the physical properties of the QDSLs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, colloidal quantum dots can be assembled into 2D arrays where photons can be absorbed [7][8][9][10][11][12][13][14][15] . As improvements in their synthesis are enabling narrower size distribution, complete surface passivation and better system assembly, building better quality 2D quantum dot arrays is becoming easier 4,[16][17][18] . This opens up new possibilities in materials engineering as quantum dots are highly configurable systems 15,19,20 .…”
Section: Introductionmentioning
confidence: 99%